2009
DOI: 10.1017/s113874160000189x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating One's Own and One's Relatives' Multiple Intelligence: A Cross-Cultural Study from East Timor and Portugal

Abstract: This study examined estimates of their own, and their parents' general and multiple intelligences. Three hundred and twenty three students from East Timor, and one hundred eighty three students from Portugal estimated their own, and their parents' IQ scores on each of Gardner's ten multiple intelligences. Men believed they were more intelligent than were women on mathematical (logical), spatial, and naturalistic intelligence. There were consistent and clear culture differences. Portuguese gave higher self, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Neto et al () found that Portuguese gave higher self and family ratings than did Macanese. A similar pattern was found in East Timor (Neto, Furnham, & Pinto, ) where students also estimated their own, and their parents' IQ scores on each of Gardner's 10 multiple intelligences. Portuguese reported higher self and family ratings than did Timorese.…”
Section: Reversal Iqsupporting
confidence: 67%
“…Neto et al () found that Portuguese gave higher self and family ratings than did Macanese. A similar pattern was found in East Timor (Neto, Furnham, & Pinto, ) where students also estimated their own, and their parents' IQ scores on each of Gardner's 10 multiple intelligences. Portuguese reported higher self and family ratings than did Timorese.…”
Section: Reversal Iqsupporting
confidence: 67%
“…The mothers make lower self-estimates than the fathers in most of the intelligences proposed. The differences are significant in four intelligences: verbal, corporal, and especially, mathematical and spatial intelligence, thus providing support to a series of studies that confirm that women make lower self-estimates of their intelligence than men (Furnham & Baguma, 1999;Furnham, Clark, & Bailey, 1999;Furnham, Fong, & Martin, 1999;Furnham & Gasson, 1998;Furnham, Rakow, & Mak, 2002;Furnham, Reeves, & Budhani, 2002;Neto et al, 2009;Visser et al, 2008). In fact, there are only a few exceptions to the confirmation of this effect (Swami, Furnham, & Zilkha, 2009).…”
Section: Discussionmentioning
confidence: 61%
“…Some of the most important research areas have been (Cruise, Lewis, and Mc Guckin (2006): gender differences in the estimation of general IQ (Beloff, 1992;Hogan, 1978), gender and intergenerational differences in the estimation of intelligence in its diverse domains (Bennett, 1996;Furnham, 2000;Ramstedt & Rammsayer, 2000), cross-cultural differences in the estimation of the diverse intelligences (Furnham & Chamorro-Premuzic, 2005;Neto, Furnham, & Pinto, 2009), the relation between intelligence estimation and personality variables (Furnham, Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most recurrent themes in the research on Multiple Intelligences Theory is the approach to the perception of lay people about sex, gender and social roles [31][32][33][34][35][36][37] . Among these, no investigations were found that contemplated the differences between the sexes of patients with altered language.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have presented the different perceptions of men and women, about their intelligence and/or their partners and/or their parents and/or their children. In most of these, it was found that there is a different understanding of the sexes in relation to the greater development of the intelligences and better performance in the activities related to them: masculine, mainly, in the spatial and logicalmathematical intelligences, and feminine, mainly in the interpersonal [31][32][33][34][35][36][37] . In this sense, when comparing the results of this investigation with these studies, it is verified that they are partially similar.…”
Section: Discussionmentioning
confidence: 99%